Upaya Guru Dalam Menangani Anak Yang Terlambat Mengenal Huruf Abjad Kelompok B Di TK Pelangi Jekani Kabupaten Sragen - Afifah, Eva Asngadzatul; Sibawaihi; Prasetyo, Sigit (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study is based on the existence of obstacles, where students have difficulty in recognizing the alphabet. In this case, collaboration between educators and parents is very necessary to overcome this problem, with handling that is adjusted to the causative factors. The purpose of this study is to describe in detail the efforts of teachers in dealing with children who are late in recognizing the alphabet in group B of Pelangi Jekani Kindergarten, Sragen Regency, and to identify the supporting and inhibiting factors that influence this delay. This study uses descriptive qualitative research with children in group B as research subjects. The focus of the study is the delay in recognizing the alphabet. Data collection was carried out through observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions/verification. Data validity testing was carried out using the triangulation method. The results of the study indicate that (1) the efforts of teachers to handle children who are late in recognizing the alphabet in group B of Pelangi Jekani Kindergarten were carried out through several stages, such as learning activities to recognize the alphabet, use of learning media, and private tutoring for children who are experiencing delays. (2) Supporting factors for this effort include providing game media, giving assignments, and consistent motivation. Meanwhile, inhibiting factors are changes in children's habits and parental negligence.